Impact of the Air-Conditioning System on the Power Consumption of an Electric Vehicle Powered by Lithium-Ion Battery. (26th December 2013) - Mebarki, Brahim; Draoui, Belkacem; Allaou, Boumediène; Rahmani, Lakhdar; Benachour, Elhadj
Abstract : The car occupies the daily universe of our society; however, noise pollution, global warming gas emissions, and increased fuel consumption are constantly increasing. The electric vehicle is one of the recommended solutions by the raison of its zero emission. Heating and air-conditioning (HVAC) system is a part of the power system of the vehicle when the purpose is to provide complete thermal comfort for its occupants, however it requires far more energy than any other car accessory. Electric vehicles have a low-energy storage capacity, and HVAC may consume a substantial amount of the total energy stored, considerably reducing the vehicle range, which is one of the most important parameters for EV acceptability. The basic goal of this paper is to simulate the air-conditioning system impact on the power energy source of an electric vehicle powered by a lithium-ion battery.